سیاسه‌تی ڕاگواستن له‌ سه‌رده‌می ئاشوری نوێ دا (‌سه‌رده‌می سارگۆنی دووه‌م و -سینحاریب به‌ نموونه‌) توێژینه‌وه‌یه‌كی مێژوویی-وه‌سفیه‌ - اسماعيل, پ.د.صلاح كانبى; احمد, شه‌ماڵ عثمان (Sulaimani Journal for Humanities, 2023)
The occupation process during the new Assyrian Empire (911-612 BC) and the deportation of the population and looting the wealth of the peoples of different regions had a bad result on the political map and demographic change in those areas where assyrian kings attacked, transporting the original population and replaced them by Assyrian population. This policy had left a negative effect on the future of the Assyrian authorities and their dominance. The relocation reached its peak during the reign of both Kings Sargon II and Sennacherib. In this research, a historical- descriptive method has been applied considering the coronology of events. This research is based on three axes, in the first axis, a summary of the deportation process in the New Assyrian era until the Sargon II era is discussed. In the second axis the deportation process during the reign of Sargon II is focused on, and the third axis is dedicated to talking about the process of occupation and deportation of nations during the reign of King Sennacherib.